Scandcleft randomized trials of primary surgery for unilateral cleft lip and palate: Speech proficiency at 10 years of age - Willadsen, E.; Jørgensen, L. D.; Alaluusua, S.; Pedersen, N. H.; Nielsen, J. B.; Hölttä, E.; Hide, Ø.; Hayden, C.; Havstam, C.; Hammarström, I. L.; Davies, J.; Boers, M.; et al. (International journal of language & communication disorders, 2023)
Background & Aim To assess consonant proficiency and velopharyngeal function in 10‐year‐old children born with unilateral cleft lip and palate (UCLP) within the Scandcleft project. Methods & Procedures Three parallel group, randomized, clinical trials were undertaken as an international multicentre study by nine cleft teams in five countries. Three different surgical protocols for primary palate repair (Arm B–Lip and soft palate closure at 3–4 months, hard palate closure at 36 months, Arm C–Lip closure at 3–4 months, hard and soft palate closure at 12 months, and Arm D–Lip closure at 3–4 months combined with a single‐layer closure of the hard palate using a vomer flap, soft palate closure at 12 months) were tested against a common procedure (Arm A–Lip and soft palate closure at 3–4 months followed by hard palate closure at 12 months) in the total cohort of 431 children born with a non‐syndromic UCLP. Speech audio and video recordings of 399 children were available and perceptually analysed. Percentage of consonants correct (PCC) from a naming test, an overall rating of velopharyngeal competence (VPC) (VPC‐Rate), and a composite measure (VPC‐Sum) were reported. Outcomes & Results The mean levels of consonant proficiency (PCC score) in the trial arms were 86–92% and between 58% and 83% of the children had VPC (VPC‐Sum). Only 50–73% of the participants had a consonant proficiency level with their peers. Girls performed better throughout. Long delay of the hard palate repair (Arm B) indicated lower PCC and simultaneous hard and soft palate closure higher (Arm C). However, the proportion of participants with primary VPC (not including velopharyngeal surgeries) was highest in Arm B (68%) and lowest in Arm C (47%). Conclusions & Implications The speech outcome in terms of PCC and VPC was low across the trials. The different protocols had their pros and cons and there is no obvious evidence to recommend any of the protocols as superior. Aspects other than primary surgical method, such as time after velopharyngeal surgery, surgical experience, hearing level, language difficulties and speech therapy, need to be thoroughly reviewed for a better understanding of what has affected speech outcome at 10 years. WHAT THIS PAPER ADDS What is already known on the subject Speech outcomes at 10 years of age in children treated for UCLP are sparse and contradictory. Previous studies have examined speech outcomes and the relationship with surgical intervention in 5‐year‐olds. What this study adds to the existing knowledge Speech outcomes based on standardized assessment in a large group of 10‐year‐old children born with UCLP and surgically treated according to different protocols are presented. While speech therapy had been provided, a large proportion of the children across treatment protocols still needed further speech therapy. What are the potential or actual clinical implications of this work? Aspects other than surgery and speech function might add to the understanding of what affects speech outcome. Effective speech therapy should be available for children in addition to primary surgical repair of the cleft and secondary surgeries if needed.